Impact localization of composite laminates based on four points localization algorithm of MXene/CNT sensors - Wang, Ying; Tiannan, Man; Lu, Shaowei; Liu, Siyu; Liu, Xinhua (Applied physics. A, Materials science & processing, 2022)
Composite laminates are susceptible to impact damage during service, and some damage is invisible. So it is necessary to monitor the impact location on the surface of composite laminates. Novel carbon nanomaterials represented by carbon nanotubes and MXene films have unique nanoscale structures and excellent physical properties. Applying the carbon nanotubes (CNT) and MXene films to monitoring the damage area of composite laminates under impact. Laying sensor arrays within the monitoring range, a localization algorithm suitable for sensor arrays is proposed, which can accurately calculate and locate the impact position to the monitoring area. Then check the impact location area, detect damage in time, and avoid structural damage or even failure caused by accumulated damage. After the impact test, the sum of the resistance change rate of the sensor in the M 5 area is 0.6030, which is higher than the sum of the resistance change rate of other areas, and the impact point is determined to be in the M 5 area. The calculation results are completely consistent with the real impact area, which greatly improves the efficiency of detection and maintenance, and has certain engineering significance.